DEVELOPING YOUNG ENTREPRENEURS IN THE FASHION FIELD THROUGH EXTRACURRICULARS ACTIVITIES - Zahro, Siti; Lyau, Nyan-Myau; Nurhadi, Didik (Home Economics Journal, 2020)
Unemployed youths constitute major problems in many countries. Ideally, they should get themselves prepared to respond to future challenges. Entrepreneurship is one of the ways they can get jobs or establish their own firms. However, to be successful entrepreneurs, they should go through a gradual process that can be prepared in the high school before they continue to the university. Thus, high school stakeholders need to develop their students' entrepreneurial flair through a learning strategy on extracurricular activities supported by lesson plans, learning processes, and evaluation. This paper aims to give a clear picture of steps to hone students' entrepreneurial skills through extracurricular activities in fashion field stimulated to prepare them for being good entrepreneurs. This program of character building depends on favorable education environments and supports from leaders, teachers and students' parents.